The effect of advanced maternal age on maternal and neonatal outcomes of placenta previa: A register-based cohort study. (August 2018) - Roustaei, Zahra; Vehviläinen-Julkunen, Katri; Tuomainen, Tomi-Pekka; Lamminpää, Reeta; Heinonen, Seppo
Abstract: Objectives: Advanced maternal age (AMA) at the time of delivery generally worsens obstetric outcomes, but its effects on specific pregnancy problems, such as placenta previa, have not been adequately assessed. Therefore, the objective of the study was to explore the effect of AMA on adverse maternal and neonatal outcomes among pregnancies complicated by placenta previa. Study Design: The study was a register-based cohort study using data of three Finnish health registries, including information of 283 324 women and their newborns. Separate multivariable logistic regression modeling was performed for women under age 35 and women aged 35 or older to assess the association between placenta previa and adverse maternal and neonatal outcomes. Furthermore, interactions between maternal age and placenta previa were tested. Results: A total of 283 324 deliveries of which 714 (0.3%) were complicated by placenta previa. Adverse maternal and neonatal outcomes increased in women with placenta previa, with different patterns across age groups. The adjusted odds ratios and 95% confidence intervals for AMA and young women with previa were 7.3 (5.0–10.6) and 6.8 (5.2–8.9) in blood transfusion, 11.3 (5.4–23.3) and 10.9 (6.1–19.6) in placental abruption. In neonatal outcomes the adjusted odds ratios for AMA and young women with placenta previa were 8.8 (6.6–11.6) and 11.7 (9.7–14.1) in preterm birth <37 weeks, 4.0 (3.0–5.3) and 4.9 (4.1–5.9) in neonatal intensive care unit (NICU) admission, 4.0 (2.8–5.7) and 5.9 (4.7–7.4) low birth weight <2500 g, 2.7 (1.5–4.9) and 3.3 (2.2–5.0) in low Apgar score at 5 min. The joint effects of maternal age and placenta previa on the risk of adverse maternal and neonatal outcomes were non-significant. Conclusions: The risk of adverse maternal and neonatal outcomes for women with placenta previa was not substantially affected by maternal age if their different risk profiles were taken into account.